1993
DOI: 10.1590/s0037-86821993000200008
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniose cutânea disseminada produzida por Leishmania viannia braziliensis no Estado do Maranhão - Brasil

Abstract: A leishmaniose dérm ica pós-calazar foi a prim eira form a disseminada da doença, descrita como seqüela do calazar indiano, caracterizandose por m últiplas lesões de pele atribuídas à Leishmania donovani610. Existe ainda outra forma d is s e m in a d a d a d o e n ç a , c o n h e c id a com o leishmaniose cutânea difusa ou anérgica, relatada inicialmente por Silva7 no Brasil e Convit2 na Venezuela.A forma abordada no presente trabalho não se refere às anteriores, e sim a uma outra manifestação clín ic a da le … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The current case draws attention to the number of lesions compared to other cases described in Brazil and in the Southern region, given that the cases of CL have been reported almost exclusively in the North and Northeast of Brazil 4,5,11 . In Maranhão State , Galvão et al 5 reported a patient with 58 lesions; Carvalho et al 8 , in the State of Bahia, found in eight patients, a number of lesions ranging from 75 to 800.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The current case draws attention to the number of lesions compared to other cases described in Brazil and in the Southern region, given that the cases of CL have been reported almost exclusively in the North and Northeast of Brazil 4,5,11 . In Maranhão State , Galvão et al 5 reported a patient with 58 lesions; Carvalho et al 8 , in the State of Bahia, found in eight patients, a number of lesions ranging from 75 to 800.…”
Section: Discussionmentioning
confidence: 95%
“…In Maranhão State , Galvão et al 5 reported a patient with 58 lesions; Carvalho et al 8 , in the State of Bahia, found in eight patients, a number of lesions ranging from 75 to 800. Turetz et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The immunological aspects are also distinct, as there is an abnormality in cellular immunity which is restored after treatment. On the other hand, in the diffuse form there is always a lack of T‐cell response, which is represented by a negative Montenegro skin test 3–5 …”
Section: Case 2 (Fig 2)mentioning
confidence: 99%